2010
DOI: 10.1007/s00432-010-0787-x
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with two recombinant Bacillus Calmette-Guérin vaccines that combine the expression of multiple tandem repeats of mucin-1 and colony stimulating-factor suppress breast tumor growth in mice

Abstract: rBCG-MVNTR4-CSF and rBCG-MVNTR8-CSF vaccines may be good candidates for breast tumor immunotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…There are several reports showing that survivin autoantibodies have been detected in some cancer patients, such as lung, breast and colorectal cancer patients (AlJoudi et al, 2006;Karanikas, 2009;Chen et al, 2010), as well antibodies to MUC1 (Hirasawa et al, 2000;Tang et al, 2010). Moreover, several studies have revealed that vaccines targeting survivin or MUC1 VNTR can elicit both specific humoral and cellular immune responses both in pre-clinical and clinical trials (Tang et al, 2008;Yuan et al, 2010;Ishizaki et al, 2011;Kameshima et al, 2011), indicating that they are potent cancer vaccine targets. However, the correlations between auto-antibodies to survivin and MUC1 VNTR remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…There are several reports showing that survivin autoantibodies have been detected in some cancer patients, such as lung, breast and colorectal cancer patients (AlJoudi et al, 2006;Karanikas, 2009;Chen et al, 2010), as well antibodies to MUC1 (Hirasawa et al, 2000;Tang et al, 2010). Moreover, several studies have revealed that vaccines targeting survivin or MUC1 VNTR can elicit both specific humoral and cellular immune responses both in pre-clinical and clinical trials (Tang et al, 2008;Yuan et al, 2010;Ishizaki et al, 2011;Kameshima et al, 2011), indicating that they are potent cancer vaccine targets. However, the correlations between auto-antibodies to survivin and MUC1 VNTR remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…SCID mice reconstituted with human PBL followed by immunization with the rBCG strains developed MUC1-specific cellular immune respnses and enhanced protection against MUC1-positive human breast cancer xenografts compared to control mice reconstituted with human PBL and immunized with non-cytokine secreting BCG. Studies have also www.intechopen.com demonstrated that the antitumor effects of the rBCG strains were correlated with the number of MUC1 tandem repeats delivered by BCG ( a Yuan et al, 2009Yuan et al, , 2010. These results suggest that these MUC1 rBCG strains coexpressing Th1-stimulating cytokines are promising candidates as breast cancer vaccines and thus deserve further investigation.…”
Section: Anti-tumor Studiesmentioning
confidence: 93%
“…Most of these cytokine-and chemokine-secreting rBCG strains showed their abilities to enhance BCG-induced cellular immune responses including Th1 cytokine production, cellular cytotoxicity, DC activation, and anti-BCG or anti-M.tb infection. Some of them even showed their antitumor effects in animal models of melanoma (Duda et al, 1995), breast cancer (Chung et al, 2003;a Yuan et al, 2009, Yuan et al, 2010, and bladder cancer (Arnold et al, 2004). Certain cytokine-secreting rBCG strains also induced humoral immune responses and Th2 cytokine production other than cellular immune responses in vitro and in vivo.…”
Section: Th1 Cytokine-secreting Rbcgmentioning
confidence: 99%
See 2 more Smart Citations